2011
DOI: 10.1073/pnas.1015994108
|View full text |Cite
|
Sign up to set email alerts
|

Slow protein evolutionary rates are dictated by surface–core association

Abstract: Why do certain proteins evolve much slower than others? We compared not only rates per protein, but also rates per position within individual proteins. For ∼90% of proteins, the distribution of positional rates exhibits three peaks: a peak of slow evolving residues, with average log 2 [normalized rate], log 2 μ, of ca. −2, corresponding primarily to core residues; a peak of fast evolving residues (log 2 μ ∼ 0.5) largely corresponding to surface residues; and a very fast peak (log 2 μ ∼ 2) associated with disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 43 publications
9
63
0
Order By: Relevance
“…In fact, TothPetroczy and Tawfik recently showed that mutations at the interior accumulate more rapidly once the surface has drifted sufficiently (35). Therefore, by lowering the tolerance for mutations at the surface, the divergence of the entire protein becomes constrained (35). Promiscuous interactions, which constrain mutations at the surface, could thereby limit the evolutionary rate of the entire protein.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, TothPetroczy and Tawfik recently showed that mutations at the interior accumulate more rapidly once the surface has drifted sufficiently (35). Therefore, by lowering the tolerance for mutations at the surface, the divergence of the entire protein becomes constrained (35). Promiscuous interactions, which constrain mutations at the surface, could thereby limit the evolutionary rate of the entire protein.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary rates were calculated using rate4site 63 as described in 18 . This method computes the relative evolutionary rate for individual protein positions across the entire phylogeny, via Bayesian Estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, stabilizing mutations, which have no effect on protein fitness on their own, are revealed as beneficial when they compensate for new-function mutations that are typically destabilizing 16 . Such stabilizing mutations can have local, specific compensatory effects 17; 18 , or global effects, when they can compensate for a whole range of destabilizing mutations 16 in non-contacting residues 19; 20; 21 . One case study of positive epistasis in the vertebrate glucocorticoid receptor revealed a mutation that was initially neutral, yet by reorienting an alpha helix, enabled the acceptance of an adaptive mutation that would be deleterious on its own 22 .…”
mentioning
confidence: 99%
“…Thus, highly expressed proteins are predicted to evolve slowly. Highly constrained protein surfaces (such as those involved in protein-protein interactions) also dictate slow evolutionary rates amongst residues in the core of the protein [53]. It remains to be elucidated whether the contributions to protein evolutionary rates of expression level or constrained surfaces are correlated with effects on catalytic efficiency.…”
Section: Whence Excessively Good Enzymes?mentioning
confidence: 99%